Nursing diagnoses in septic patients: Association with signs, symptoms and SOFA score - Bubols , Jessica Pinheiro; Michielin, Fabiano da Costa; Machado , Elisiane de Oliveira; Nemetz, Betina; Silva , Fabio Viegas da; Wachter , Djulia Andriele; Vizini , Simone Thais; Santos, Suimara; Chassot , Maicon Daniel (Seven Editora, 2024)
Objective: To associate nursing diagnoses (ND) with signs/symptoms and SOFA score in septic patients. Methods: Retrospective cross-sectional study that analyzed 242 medical records. Results: The most prevalent sign was leukocytosis (42%). The average SOFA score was 7 (53.3%). The prevalent NDs with a significant association were: Risk of Infection (IR) (86%); Self-Care Deficit Syndrome (SDA) (68%) and Impaired Spontaneous Ventilation (EPV) (54.1%). SOFA >7 was associated with IR (p=0.002); SDA (p